2020
DOI: 10.1039/d0nr01495h
|View full text |Cite
|
Sign up to set email alerts
|

High charge carrier mobility in solution processed one-dimensional lead halide perovskite single crystals and their application as photodetectors

Abstract: Large space-charge limited mobility and a fast optical response is reported in low dimensional halide perovskite crystals. A transition between hopping transport and band-like transport is observed at 200 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The observed defect-independent carrier diffusion coefficient is well consistent with the results of temperature-dependent charge mobility measurements [6,7,[33][34][35]. Zhu et al have recently explained this phenomenon by the formation of large polarons (strong electron (hole)-phonon coupling) in perovskite, which may ''protect" the carriers from both scattering and defect trapping [36].…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The observed defect-independent carrier diffusion coefficient is well consistent with the results of temperature-dependent charge mobility measurements [6,7,[33][34][35]. Zhu et al have recently explained this phenomenon by the formation of large polarons (strong electron (hole)-phonon coupling) in perovskite, which may ''protect" the carriers from both scattering and defect trapping [36].…”
supporting
confidence: 80%
“…Therefore, elaborating the correlation of the defect density with carrier transport kinetics is crucial for designing and optimizing perovskite materials and further improvement of the device performance. Microwave conductive and transient THz measurements have shown that charge mobility (l) in perovskite follows a simple temperature-dependent response by l / T À2/3 [6,7]. This T À2/3 dependence is indicative of free carrier transport limited majorly by acoustic phonon scattering rather than impurity scattering.…”
mentioning
confidence: 99%
“…[ 1,2 ] As such, they have resulted in remarkable progress in the development of a wide variety of (opto‐)electronic devices, including solar cells, [ 3–6 ] light emitting diodes (LEDs), [ 7–9 ] lasers, [ 10–12 ] thermoelectric generators, [ 13–15 ] and photodetectors. [ 16–18 ] Among them, perovskite solar cells (PSCs) have rapidly emerged as one of the hottest topics in the photovoltaics community owing to their high power‐conversion efficiencies (PCE), and the promise to be produced at low cost. [ 19–32 ] The most extensively studied perovskites for solar cells are 3D halide perovskites with the general chemical formula of ABX 3 , where A can be Cs + , CH 3 NH 3 + (MA + ), or HC(NH 2 ) 2 + (FA + ), B can be Ge 2+ , Sn 2+ , or Pb 2+ and X can be Cl − , Br − or I − .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] In 1950s, the crystal structures of CsPbX 3 were determined via X‐ray diffraction and the photoconductivity was demonstrated by Moller. [ 2,3 ] It had been largely overlooked in scientific fields until recent years, when perovskite semiconductors were found to have great application prospects in photovoltaics, [ 4–6 ] optoelectronics, [ 7–11 ] and catalysis [ 12,13 ] etc., for their high carrier mobility, [ 14–16 ] long diffusion lengths, [ 17,18 ] high photoelectric conversion efficiency, [ 19 21 ] and high fluorescence quantum yield. [ 22–25 ] Based on CsPbX 3 , devices of photodetectors, [ 26–28 ] light‐emitting diodes, [ 29,30 ] lasers, [ 31–33 ] chemical sensors, [ 34,35 ] and X‐ray detectors [ 36–38 ] have been developed.…”
Section: Introductionmentioning
confidence: 99%